To survive or perish, Nyoman and Ketut existences at stake! - Ida Bagus Gede Karyambara Putra (Bali Tourism Board, 2019)
Governor of Bali, Dr. Ir. I Wayan Koster, M.M. recently instructed his regents through Governor Instruction Number 1545 of 2019 to promote Krama Bali Family Planning (KBFP); a ‘four children policy’ instead of National family planning program (FPP) a ‘two children policy’. The central government deployed FPP as an effective way to prevent population explosion in the last fifty years; which is highly crucial to ensure the society’s welfare in future. In contrast, apparently, from the Governor of Bali, Wayan Koster’s perspective, the program is subduing Balinese society growth, and threatening the survivability of the third and fourth child generations (Nyoman and Ketut). Through the Instruction, it is expected the Balinese family would decide to have more than two children, as the Governor’s wish to protect the ancestral noble heritage. In these times, there are several things that a family should be taken into account before deciding to follow KBFP program; from the female side agreement, family’s cashflow condition, and recent demographic situation of Bali that has been expanding rapidly for years. Nevertheless, the instruction is not sternly applied, since there is no sanction for the society who wish not to follow the government’s suggestion. As a verdict, a Balinese family still own the power to decide independently what they may find suitable for their future.